Customised enriched acoustic environment for sound therapy of tinnitus - Cobo Pedro; Cuesta María; de la Colina Carlos (Acta Acustica, 2021)
Tinnitus is an auditory disorder very difficult to treat. Whereas up until now there is not a “cure” for tinnitus, the most extended treatment combines counselling with sound therapy. When this sound is a broadband noise in the audio frequency band, this protocol is named tinnitus retraining therapy. Even though broadband noise was proposed at the beginning as the stimulus for sound therapy, many other sounds have been subsequently proposed and used, including tones, noise bands, music, and nature sounds. Although any sound, low enough to avoid annoyance, discomfort or hearing damage, is better than silence for tinnitus treatment, it is not still clear the relationship of the success of the therapy with the properties of the sound stimuli. The aim of this article is to propose an optimal sound treatment that provides a precise and selective stimulation of the whole auditory system. The proposed sound stimulus, Enriched Acoustic Environment, consists of sequential tones or broadband noise matched to the HL curves of the patients. The acoustical characteristics of these stimuli are analyzed and their positive effects in the treatment of subjects with tinnitus are reported.